Exploring The Role of Transformational Leadership in Enhancing Employee Engagement: a Qualitative Study in Contemporary Work Environments - Fatmawati A Rahman; Ardhie Goeliling; Abdurrahman Achmad; Rince Tambunan; Rezqi Sri Saleko Putri (PT. Maju Malaqbi Makkarana, 2026)
The rapid transformation of contemporary work environments driven by digitalization, hybrid work systems, and evolving workforce expectations has intensified the need for effective leadership approaches that foster employee engagement. This study aims to explore the role of transformational leadership in enhancing employee engagement within contemporary organizational contexts using a qualitative research design. Guided by a phenomenological approach, data were collected through in depth semi structured interviews with employees who had direct supervisory relationships in digitally mediated or hybrid work settings. Thematic analysis revealed four major themes: visionary inspiration and meaningful work, individualized support and psychological safety, intellectual stimulation and professional growth, and trust based relationships and organizational identification. The findings indicate that transformational leadership strengthens employee engagement by cultivating meaningfulness, empowerment, trust, and intrinsic motivation, which collectively enhance employees’ physical, cognitive, and emotional involvement in their work roles. The study extends existing leadership and engagement theories by providing contextualized insights into how transformational leadership is experienced in modern organizational environments. Practically, the findings highlight the importance of developing transformational competencies among leaders to sustain engagement and performance in increasingly complex and interconnected workplaces